Macro Determinants on Non-Performing Loans of Indonesia Commercial Banks (Credit Risk Scenario) - Hariyanti, Dini (Jurnal Manajemen Indonesia, 2024)
A stable financial system is significant for an economy. Commercial banks play a critical role in facilitating the flow of credit and boosting the productivity of businesses through investment funding. In addition to receiving deposits, commercial banks provide loans to customers, exposing them to credit risk in the form of non-performing loans (NPL). This study aims to analyze the determinants of NPL and stress-test macro variables in the Indonesian banking system. The findings of this study, which used a data panel (Stata 17) and the Monte Carlo Stressing test of the Value at Risk (VAR) approach by studying a sample of 43 Commercial Banks listed on the IDX from 2008.1 to 2023.4, are significant. The main findings are Non-Performing Loan lag -1 (NPLt-1), Loan Deposit Ratio (LDR), Interest rate (SBI) and inflation (INF), and the significance of Non-Performing Loan (NPL). The results of the NPL Stress Scenario based on the VaR approach with interest rate and inflation shock carried out are still much lower than based on the provisions of Bank Indonesia Regulation Number 06/10/PBI/2004 concerning the Health Level Assessment System for Commercial Banks, the NPL ratio is 5 percent. It can be concluded that the NPL condition of commercial banks in Indonesia from 2008 to 2023 is still below the specified limit to face serious credit problems. These significant findings can engage and interest the audience, particularly those involved in the Indonesian banking system and macro prudential policies, and provide them with valuable insights. Keywords—Commercial Banks; Non-Performing Loan; Value at Risk